(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The attitudes of customers are undergoing a shift with regards to the environment, fostering aclimate of innovation aimed at conservation. The resultant benefits derived from this innovativeapproach are expected to endure beyond the present generation. This study examines the perceptionsand attitudes of consumers towards environmental conservation, as well as their purchase patterns inrelation to eco-friendly items. This report also examines the effectiveness of marketing activities inraising consumer awareness of green products. This study further examines consumer behavior and theinfluence of marketing communication in order to ascertain the factors that motivate consumers tochoose environmentally friendly products. This study presents the findings of a consumer productsurvey that utilized a questionnaire derived from the environmental survey and the Worldwideenvironmental behavior survey. This article examines the insufficient exposure of consumers tomarketing communication regarding green products and proposes an increased utilization of marketingstrategies and brand promotion to effectively market and sell environmentally friendly items. The reportposits that there is untapped potential in the Indian market for environmentally friendly products,particularly among customer segments who prioritize environmental concerns.